Learning and memory are impaired in the object recognition task during metestrus/diestrus and after sleep deprivation - Cordeira, Joshua (Behav Brain Res, 2017)
Females are an under-represented research model and the mechanisms through which sleep loss impairs cognition are not clear. Since levels of reproductive hormones and the estrous cycle are sensitive to sleep loss and necessary for learning and memory, we hypothesized that sleep deprivation impacts learning and memory in female mice by interfering with the estrous cycle. We used the object recognition task to assess learning and memory in female mice during separate phases of the estrous cycle and after sleep loss. Mice in metestrus/diestrus attended to sample objects less than mice in proestrus/estrus during object acquisition, the first phase of the object recognition task. Subsequently, during the recognition phase of the task, only mice in proestrus/estrus displayed a preference for the novel object. Sleep deprivation for 12h immediately before the object recognition task reduced time attending to sample objects and novel object preference for mice in proestrus/estrus, without changing length of the estrous cycle. These results show that sleep deprived mice in proestrus/estrus had learning deficits and memory impairments, like mice in metestrus/diestrus. Since sleep deprivation did not disrupt the estrous cycle, however, results did not support the hypothesis. Cognitive impairments due to acute sleep loss were not due to alterations to the estrous cycle.